Treatment of pemphigus in Australia: Aligning current practises with global recommendations. (20th February 2022) - Somerville, Erin; Gebauer, Kurt; Mclean‐Tooke, Andrew
ABSTRACT: Pemphigus encompasses of a group of rare, and often severe, intraepidermal bullous dermatoses that are mediated by autoantibodies that act against adhesion proteins of the desmosome. The current international consensus is that the use of intravenous CD20 inhibitors should be first‐line in the management of moderate‐to‐severe cases of pemphigus, however Australia is yet to adopt this. Systemic corticosteroids, combined with conventional corticosteroid‐sparing immunosuppressive agents such as azathioprine, mycophenolate mofetil, cyclosporin and methotrexate is still recommended as first‐line therapy in Australia despite overwhelming evidence that combining rituximab with a rapid corticosteroid tapering regime is more effective in the treatment of moderate‐to‐severe pemphigus, and leads to fewer severe adverse effects. We propose a therapeutic approach that echoes the international consensus and recommend that rituximab, an anti‐CD20 monoclonal antibody, be listed in the formularies of Australian Public Hospitals and on the Pharmaceutical Benefits Scheme for use in moderate to severe pemphigus.